The Ghosts of the Past : Latin Literature, the Dead, and Rome's Transition to a Principate - Dufallo, Basil; Project Muse. (Columbus : The Ohio State University Press, 2007)
"To understand the literary life of the Roman dead, The Ghosts of the Past develops a new perspective on Latin literature's interaction with Roman culture. Drawing on the insights of sociology, anthropology, and performance theory, Basil Dufallo argues that authors of the late Republic and early Principate engage strategically with Roman behaviors centered on the dead and their world in order to address urgent political and social concerns. Republican literature exploits this context for the ends of political competition among the clan-based Roman elite, while early imperial literature seeks to restage the republican practices for a reformed Augustan society." "Calling into question boundaries of genre and literary form, Dufallo's study will revise current understandings of Latin literature as a cultural and performance practice. Works as diverse as Cicero's speeches, Propertian elegy, Horace's epodes and satires, and Vergil's Aeneid appear in a new light as performed texts interacting with other kinds of cultural performance from which they might otherwise seem isolated."
Introduction: The dead as living -- Oratory and magic in Republican Rome -- Domesticae furiae : Cicero's tragic universe -- The Second Philippic as cultural resistance -- Propertian elegy as "restored behavior" -- Vergil's alternatives to Republican performance -- Conclusion: The living as the dead.
Description based on print version record.
Keywords: Latin literature; Dead in literature; Morts dans la litterature; Litterature latine -- Histoire et critique; Dead in literature; Latin literature -- History and criticism; Criticism, interpretation, etc; Electronic books